Welcome from UNESCO - Jokl, E. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
Once again it is my privilege to convey to this meeting the good wishes of the UNESCO International Council of Sport and Physical Education. The Council, which sponsored the first symposium on "Biomechanics of Swimming," was glad to do so again. It is very appreciative of the fine work done by the organizers of today's event, especially by Dr. Lewillie, Dr. Clarys, Dr. Nelson, Dr. Morehouse, and Dr. Hebbelinck. It is with pleasure that the Council complies with the wish for a Working Group on "Biomechanics of Swimming" henceforth to be directly associated with its Research Committee. The Group can rest assured that every support it may need from the Committee will be forthcoming.